Navigating Critical Thinking Skill Development through Interactive Virtual Reality - Firdaus, Muliawan; Mukhtar, Mukhtar; Darari, Muhammad Badzlan (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study investigates the effectiveness of interactive Virtual Reality (VR) in enhancing critical thinking skills among third-year Mathematics Education students in a calculus course. Using a quasi-experimental design, 122 students were divided into experimental and control groups. Over seven weeks, the experimental group used the CalcVR application for interactive problem-solving, while the control group followed traditional methods. Pre- and post-tests showed significant critical thinking improvement in the experimental group (p < 0.05), supported by large effect sizes. Qualitative data highlighted the immersive and engaging nature of VR in fostering analytical and inferential skills. The study recommends further exploration of VR in diverse disciplines, extended interventions, and integrating AI for personalized learning. Limitations include the focus on one course and a short intervention period.